"You Don't Know Me, But ...": Access to Patient Data and Subject Recruitment in Human Subjects Research - Schonfeld, Toby; Brown, Joseph S.; Amoura, N. Jean; Gordon, Bruce (American journal of bioethics, 2011)
In this article, we argue that maintaining a patient's right to provacyis an essential factor in determining who has legitimate access to patient information. Our thesis is that access to patient information for recruitment or screening for research must not violate a patient's provacy. That is, we argue that HIPAA's permissibility unethically expands the number of people with access to private patient information. Adapted from the source document.